The Mechanism of Electro-Catalytic Oxidation of Glucose on Manganese Dioxide Electrode Used for Amperometric Glucose Detection. Issue 11 (1st January 2018) - Handa, Yutaka; Watanabe, Kensuke; Chihara, Kuniko; Katsuno, Eiji; Horiba, Tatsuo; Inoue, Masayuki; Komaba, Shinichi
Abstract : Electrolytic manganese dioxide (EMD) is applied as a non-enzymatic glucose-oxidizing electrode catalyst. To elucidate the electrochemical oxidation mechanism of glucose, the catalytic activity of EMD is examined in a phosphate buffer solution by comparing electro-catalytic decomposition behaviors of four saccharides, glucose, deoxyglucose, ribose, and deoxyribose, with consideration of equilibration of their molecular transformation. We find that anodic decomposition of glucose and ribose is catalyzed at the EMD electrode, however no catalytic behaviors of deoxyglucose and deoxyribose are observed. The catalytic activity is influenced by pH and temperature conditions. Form these observations, it is believed that the anodic decomposition is attributed to the enediol transformation of glucose and ribose and is not attributed to the aldehyde transformation of four saccharides. Because the EMD catalyst for glucose oxidation does not have good selectivity to glucose unlike enzyme electrode, polyion complex (PIC) layer formed onto the surface of EMD electrode by simple drop-cast method was further applied to effectively suppress the interference by typical interferences of ascorbic acid and uric acid, which is due to PIC's molecular sieving ability. The PIC-modified EMD electrode exhibited superior glucose response with a wide detection range of 0.7 and 7.5 mmol dm −3 glucose.